Peran Orang Tua dalam Mendampingi Perkembangan Akhlak Anak Usia Dini dari Pengaruh Konten Youtube pada Usia PAUD - Najamudin Najamudin; Dwi Muliati; Amelia Agustin; Mansur Tenis (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Digital transformation has significantly altered early childhood learning patterns. Platforms such as YouTube have become dominant media consumed by preschool children. Exposure to digital content during the golden age potentially affects moral development, as children remain in a critical phase of imitation and value internalization. This study aims to conceptually analyze the role of parents in assisting early childhood moral development amid YouTube exposure from an Islamic education perspective. The research employs a qualitative approach using a systematic literature review of reputable national and international journals published between 2020–2026. The analysis involves identification, inclusion-exclusion selection, thematic categorization, and critical synthesis. Findings reveal that effective moral development is strongly influenced by parental mediation patterns, including active mediation, screen-time limitation, Islamic value-based content selection, reflective dialogue, and digital role modeling. The study proposes an integrative Islamic-based digital parenting model combining modern moral development theory and Islamic tarbiyah principles. Theoretically, this study contributes by integrating family digital literacy with Islamic moral education within contemporary educational discourse.